TAREKAT SYATTARIYAH DAN PERUBAHAN SOSIAL DI CIREBON : - Ivan Sulistiana (Jurnal Dialog, 2017)
Tarîqah as a spiritual organization has grown so rapidly as to the dynamics of Islamization in Indonesia. However,tharîqah today is often stigmatized as a passive organization which contributes nothing to the community due to its religious exclusivism focusing on vertical relationship between man and God. This stigma, on the contrary, was falsely proven by the findings of a tharîqah in Cirebon. Shattariah tharîqah in Cirebon plays an active role in the dynamics of social change in the palace, in the boarding schools, and in the batik industry. By using structuration theory analysis, it can be seen that the Shattariah tharîqah contributes to: firstly, the establishment of the institution of the palace, schools, and the batik industry; secondly, to the synergies between tradition and modernization in the midst of social change in Cirebon.